Hering-Breuer Reflex and pre-Botzinger Complex: A Literature Survey - Ahmed, M (Journal of Bangladesh Society of Physiologist, 2008)
The existence and physiological role of Hering-Breuer reflex and pre-Botzinger complex has long been depreciated by the Bangladesh society of physiologist (personal communication). The aim of this mini review is to highlight the recent findings on the aforementioned topics. Due to the difficulties in vivo studies in human subjects, many aspects of the neuronal regulation of the respiratory rhythm are still unclear. However, the recent localization of the pre-Botzinger complex in humans and advances in technologies necessitates further exploration of the neuronal circuits in the pre-BotC complex which will subsequently unwrap the magical box and pave the way to solve the puzzle of the mechanism of respiratory rhythmogenesis and its modulation in different pathophysiological conditions. Key Words: Physiology; Hering-Breuer reflex; pre-Botzinger complex; Rhythmic respiration DOI:10.3329/jbsp.v2i0.988 J Bangladesh Soc Physiol. 2007 Dec;(2):89-94.